Molecular identification of the source of an uncommon tularaemia outbreak, Germany, autumn 2016 - Jacob, Daniela; Zanger, Philipp (Eurosurveillance, 2019)
Background In 2016, an uncommon outbreak of oropharyngeal tularaemia involving six human cases occurred in Germany, caused by drinking contaminated fresh must after a grape harvest. Aim We describe the details of laboratory investigations leading to identification of the outbreak strain, its characterisation by next generation sequencing (NGS) and the finding of the possible source of contamination. Methods We incubated wine samples in different media and on agar plates. NGS was performed on DNA isolated from young wine, sweet reserve and an outbreak case’s lymph node. A draft genome of the outbreak strain was generated. Vertebrate-specific PCRs using primers targeting the mitochondrial cytochrome b gene and product analyses by blast search were used to identify the putative source of must contamination. Results No bacterial isolate could be obtained. Analysis of the draft genome sequence obtained from the sweet reserve attributed this sequence to Francisella tularensis subsp. holarctica, belonging to the B.12/B.34 phylogenetic clade (erythromycin-resistant biovar II). In addition, the DNA sequence obtained from the case’s isolate supported our hypothesis that infection was caused by drinking contaminated must. The vertebrate-specific cytochrome b sequence derived from the young wine and the sweet reserve could be assigned to Apodemus sylvaticus (wood mouse), suggesting that a wood mouse infected with F. tularensis may have contaminated the must. Conclusion The discovered source of infection and the transmission scenario of F. tularensis in this outbreak have not been observed previously and suggest the need for additional hygienic precautionary measures when processing and consuming freshly pressed must.